Problems in the Procurement Process in Libraries: An Evaluation of Canceled Tenders - Alır Derbent, Gülten; Soylu, Demet (Information World, 2025)
In the management process of libraries, efforts are made to meet their needs by ensuring the harmonious administration of five key elements: budget, personnel, users, collections, and physical space. In this context, the tendering method is frequently used to meet the various organizational needs of the libraries. However, tenders can be canceled for various reasons after lengthy and intensive bureaucratic procedures. Canceled tenders mean the initiation of an entirely new tender preparation process, resulting in time loss, increased workload, and the failure to meet needs. The purpose of this study is to identify the reasons for the cancellation of tenders conducted by administrations for libraries, to reveal the problems experienced during the tender processes, and to offer recommendations for library managers, practitioners, and regulators on improving the procurement processes. For this purpose, a content analysis was conducted to analyze the canceled tenders carried out by library administrations between 2010 and 2024 (June), as listed on the Electronic Public Procurement Platform (EKAP). The research results indicate that the primary reasons for tender cancellations are, respectively: the absence of bidders, tenders’ exceeding the estimated cost, and the absence of valid bidders. In terms of canceled tender areas, construction and building works rank highest for libraries affiliated with the General Directorate of Libraries and Publications (KYGM), municipal libraries, and university libraries. In school libraries, furniture and furnishing are prioritized. The years 2021, 2022, 2023 witnessed the highest rates of tender cancellations. The findings suggest that these cancellations are attributed to economic factors such as financial crisis and insufficient library budgets, as well as lack of knowledge and experience among library staff regarding complex tender processes. It is recommended that, during periods of crisis, should be handled with a proactive approach with planning should be made taking the risk of tender cancellations into account.